2021
DOI: 10.1101/2021.01.27.428512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pore structure controls stability and molecular flux in engineered protein cages

Abstract: Protein cages are a common architectural motif used by living organisms to compartmentalize and control biochemical reactions. While engineered protein cages have recently been featured in the construction of nanoreactors and synthetic organelles, relatively little is known about the underlying molecular parameters that govern cage stability and molecular flux through their pores. In this work, we systematically designed a 24-member library of protein cage variants based on the T. maritima encapsulin, each fea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 90 publications
(177 reference statements)
0
14
0
Order By: Relevance
“…This observation has important implications for efforts to engineer the pores of encapsulin nanocages. Where early efforts to widen the five-fold pores have demonstrated an increase in mass-transport of model substrates across the encapsulin shell (26), more recent investigations into pore modifications have shown that the shell does not act as a strong barrier to the passage of the small lanthanide substrates tested (27). Our results provide an explanation for these observations, where a dynamic and flexible pore would not act as a barrier to the passage of small ligands, such as divalent cations, across the shell.…”
Section: Structural Dynamics In the Pentameric Vertices Of The Encapsulin Shellmentioning
confidence: 99%
“…This observation has important implications for efforts to engineer the pores of encapsulin nanocages. Where early efforts to widen the five-fold pores have demonstrated an increase in mass-transport of model substrates across the encapsulin shell (26), more recent investigations into pore modifications have shown that the shell does not act as a strong barrier to the passage of the small lanthanide substrates tested (27). Our results provide an explanation for these observations, where a dynamic and flexible pore would not act as a barrier to the passage of small ligands, such as divalent cations, across the shell.…”
Section: Structural Dynamics In the Pentameric Vertices Of The Encapsulin Shellmentioning
confidence: 99%
“…Pores in the nanocompartment regulate the molecular flux through the shell by size and by charge [6,53,81,82], and constitute one of the key parameters in controlling encapsulated protein activity [83]. Their role as a molecular sieve is thought to assist the flux of correct substrates [36,49], preventing undesired reactions.…”
Section: Effect Of Encapsulin On Cargo Protein Functionmentioning
confidence: 99%
“…Encapsulins are usually further purified by SEC or ion-exchange chromatography, with a final SEC polishing step. For some applications, high resolution SEC has been deemed essential [82].…”
Section: Encapsulin Expression and Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Encapsulin nanocompartments have recently emerged as a particularly versatile bioengineering tool, resulting in their application as bionanoreactors, targeted delivery systems, and nano-and biomaterials production platforms. [8][9][10][11] Encapsulins are icosahedral protein nanocages found in bacteria and archaea with triangulation numbers of T=1 (24 nm), T=3 (32 nm) or T=4 (42 nm) containing sub-nanometer pores at the symmetry axes. 12 They self-assemble from a single HK97-fold capsid protein into 60mer (T=1), 180mer (T=3) or 240mer (T=4) protein cages and are involved in oxidative stress resistance, [13][14][15][16] iron mineralization and storage, 17,18 and sulfur metabolism.…”
Section: Introductionmentioning
confidence: 99%